Red wine polyphenols modulate bone loss in the ovariectomized rat model of postmenopausal osteoporosis - PASSALI, C.; PATSAKI, A.; LELOVAS, P.; ALIGIANNIS, N.; MAKROPOULOU, M.; KOURKOULIS, S.; PAPAIOANNOU, N.; MITAKOU, S.; SKALTSOUNIS, A.L.; DONTAS, I. (Journal of the Hellenic Veterinary Medical Society, 2019)
The aim of this study was to examine the effect of Red Wine Polyphenols (RWPs) extract on bone mineral density (BMD) in the ovariectomized (OVX) rat model. Thirty-five 10-month-old Wistar rats were separated into controls (CTRL), OVX and OVX plus RWPs in their drinking water (dose, 50 mg/kg body weight per day), starting immediately after OVX for 6 months. Βody and uterine weight, BMD of the tibia at baseline, 3 and 6 months post-OVX, and 3-pointing bending of the femur, were examined. Statistical comparison of the total tibia BMD within groups during the study period showed a significant reduction in the OVX and OVX+RWPs groups both from baseline to 3 and 6 months and from 3 to 6 months, whereas in the CTRL group, there was no significant change. For the proximal tibial metaphysis, comparison of BMD percentage changes from baseline to 3 months and 6 months and from 3 to 6 months revealed highly statistical differences between OVX and OVX+RWPs groups (P = 0.000). OVX induced a significant reduction of biomechanical parameters as expected; the 3-point bending test showed that the maximum force before fracture, energy absorption and fracture stress significantly increased in the OVX group treated with RWPs compared with the nontreated OVX rats (P = 0.048, P = 0.002 and P = 0.003, respectively). Dietary intake of RWPs for 6 months significantly prevented trabecular bone loss and improved bone strength in estrogen-deficient ovariectomized rats.